BCH DECODER MODELING AND IMPLEMENTATION ON DVB-T 2K BASEBAND - (NIM 23207128), FATIMAH
To make hardware implementation easier, modeling is written in bit-precision approach. The baseband modeling covers both transmitter and receiver sides. Models are written according to baseband moduls based on DVB-T standard. The model consist of scrambler/descrambler, RS encoder (255, 239, t=8), outer interleaver/deinterleaver, convolutional encoder, inner interleaver/deinterleaver, pilot generator, TPS generator, frame/deframe adaptation, BCH encoder/decoder (127, 113, t=2). DVB-T baseband model performance with ideal channel (without noise) gives zero error rate for all mapper types and puncture rates in the standard.